The suppression of cavitation surge in a double-suction centrifugal pump by using branch-type and slit-type accumulations installed at a pump outlet pipe. Issue 3 (March 2019) - Maeda, T; Tsuru, W; Kang, D; Tsuneda, T; Kagawa, S; An, B; Nohmi, M; Yokota, K
Abstract: Recently, cavitation surge was one of cavitation instabilities in high performance turbopumps and it damaged to a hydraulic system. In the present research, the experiments were carried out in order to investigate the influences of the branch-type and slit-type accumulators installed at a discharge pipe on cavitation surge. The experiments were conducted by the closed-type water tunnels. As a result, the occurrence region of cavitation surge in the V-shaped suction performance curve was reduced by the branch-type accumulator and the pressure amplitudes due to cavitation surge were decreased by the slit-type accumulator.